Markedly Elevated Serum Level of T-Helper Cell 17-Related Cytokines/Chemokines in Acute Myelin Oligodendrocyte Glycoprotein Antibody-Associated Optic Neuritis - Kang, Hao; Li, Hongyang; Ai, Nanping; Liu, Hongjuan; Xu, Quangang; Tao, Yong; Wei, Shihui (Frontiers in Neurology, 2020)
Purpose: The purpose of this study was to examine the differences in immunopathogenesis based on the cytokine/chemokine profiles in Myelin oligodendrocyte glycoprotein antibody (MOG-IgG) positive and negative groups. Methods: We measured the levels of Th17 cells related cytokines/chemokines in 74 serum samples, which were divided into 4 groups: healthy control (HC) group (n=15), idiopathic demyelinating optic neuritis (IDON) group (n=20), aquaporin 4 (AQP4)-IgG positive ON group (n=18), and MOG-IgG positive ON group (n=21). Serum IL17, IL21, IL28, IL31, CXCL1, CXCL2, CCL2, CCL11, CCL20 and LT-α were detected. Results: The serum of the MOG-IgG positive ON patients showed an obvious elevation of Th17 cells related cytokines/chemokines compared with that of all the MOG-IgG negative ON patients. Serum IL17, IL21 were significantly higher in the ON patients with MOG-IgG positive than in all the other 3 groups. The serum levels of IL28, IL31, CXCL1 and CCL11 were higher in the ON patients with MOG-IgG positive than in the HC group and the IDON group. The serum concentration of CCL2, CXCL2 and CCL20 in the MOG-IgG positive and AQP4-IgG positive group is higher than that of the HC group. No difference in serum LT-α level was found among the 4 groups. Adjusted multiple regression analyses showed a positive association of IL17 and IL21 levels with the serum concentration of MOG-IgG in the ON patients. Conclusion: The elevated serum level of Th17 cells related cytokine/chemokines may play an important role in the pathogenesis of MOG-IgG positive demyelinating ON.